AL-‘ATHIFAH WA DAURUHA AL-FANNI FI ITSARATI AL-MAMDUHIN: العاطفة ودروها الفني فى إثارة الممدوحين - Dahiru Sani; Amirul Mukminin; Aisyatul Hanun (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
The art of praise is considered one of the most famous arts of Arabic poetry, through which many poets have entered since the inception of the Arab dibba. Rather, it has become one of the main purposes in Arabic poetry. It is a wide arena in which poets use their charming words and meanings to attract the attention of those praised by sultans, princes, rulers, and others. So that by praising them with the most beloved qualities and good morals, as stated by Professor Abbas Mahmoud Al-Akkad, “The praiser does not satisfy his prince unless he describes his person and elaborates on describing him with the most beloved qualities to him, as a child does when he praises you and extends his hand to the sugar in your hand, and he does not hide from you that he says the good word to take after it the sweet sugar.